The semantic field of modal certainty : a corpus-based study of English adverbs - Simon-Vandenbergen, A. M. (Topics in English linguistics, 2007)
"This book provides a detailed account of the syntactic, semantic and pragmatic properties of modal adverbs of certainly in present-day English. Methodologically if relies on three types of data: monolingual corpora, translation corpora and informant testing. It is the first in-depth study in which the semantic field of certainly as realised by English adverbs is explored, combining rich information on English as well as opening up perspectives for further empirical and theoretical research into modality."--Jacket.